Emerging Importance of Supply Chain Attitudes - Andrea Rankl; Péter Németh (Chemical Engineering Transactions)
The nature of relationships within supply chains and understanding the dynamics of interactions between the supply chain members are key factors in today's globalised economy, where speed, efficiency and flexibility in the flow of goods and information are crucial. Improving the efficiency of supply chains and managing their inherent risks has become one of today's most pressing economic challenges, directly affecting not only the competitiveness of companies but also the achievement of sustainability goals. To better understand those relations among companies, a deeper understanding of the attitudes of the different supply chains is inevitable. This paper is the inaugural work towards this research. Analysing attitudes towards relationships within supply chains is a critical aspect of understanding interactions between companies and the performance of networks. Digital transformation, depth of customer integration, relationship engagement, and efficiency in joint problem-solving are factors that have a significant impact on supply chain flexibility and performance. To achieve sustainability and resilience, companies need to adopt adaptive and proactive strategies that can address environmental, social and economic challenges and anticipate and respond to future market changes. The projected aim is to understand the attitude of the organisation as an independent entity, not as an attitude generated by the individuals of the management.